The doe boy - Duval, James 1972-; Anderson, Kevin 1960-; Arredondo, Jeri; Tootoosis, Gordon 1941-2011 (Wellspring Media, 2006)
This coming-of-age films tells the story of Hunter, a half Cherokee with hemophilia (a "white man's disease"), whose teen angst is compounded by his confusing cultural identity. With an overprotective mother and a distant father, Hunter learns from his grandfather the courage to find the love he desperately seeks